أنماط التعلم والتفكير السائدة لدى تلاميذ السنة الخامسة ابتدائي - لعجال, سعيدة; ابراهيمي, سامية (جامعة الوادي University of Eloued, 2018)
هدفت الدراسة الحالية إلى التّعرف على أنماط التعلم والتفكير(أيمن، أيسر، تكامل) السائدة لدى التلاميذ ذوي صعوبات تعلم الرياضيات والكشف عن علاقتها بالاتجاه نحو مادة الرياضيات، حيث تكونت عينة الدراسة من(30) تلميذ وتلميذة من تلاميذ السنة الخامسة ابتدائي، تمّ اختيارهم عن طريق العينة القصدية وذلك للعام الدراسي (2013/2014) ببعض المدارس الابتدائية- مدينة المسيلة-. حيث طبق عليهم اختبار "تورانس"لأنماط التعلم والتفكير" ومقياس الاتجاه نحو مادة الرياضيات لـ( أبو زينة والكيلاني، 1980). وبعد عرض وتحليل نتائج الدراسة باستخدام" الرزمة الإحصائية للعلوم الاجتماعية"IBM SPSS Statistics24 لاختبار الفرضيات عن طريق المتوسطات والانحرافات المعيارية و معامل ارتباط" بيرسون" للتّحقق من وجود العلاقة. أسفرت النتائج التي كانت وفقا لفرضيات الدراسة عن: سيادة النمط الأيمن لدى عينة الدراسة، وعدم وجود علاقة ارتباطية دالة إحصائيا بين أنماط التعلم والتفكير(الأيمن، الأيسر، المتكامل) والاتجاه نحو مادة الرياضيات. وفي الأخير توّجت الدراسة بجملة من التّوصيات والاقتراحات. The current study aimed to identify styles of learning and thinking (left, right, integrated) among students with mathematics learning disabilities and reveal their relationship with the attitudes towards mathematics. The study sample consisted of (30) male and female of fifth-year primary school pupils, where they have been selected in purposive way for academic year (2013/2014) from some primary schools in M’sila City. Scales of Styles of learning and thinking developed by Torrance and the Attitudes towards Mthematics (Aabozina& Alkaylani, 1980) were administered. After presenting and the analyzing the study results using the statistical package for the social sciences, IBM SPSS Statistics, 24 to test the hypotheses through averages, standard deviations and Pearson correlation coefficient to verify the relationship. Results showed that, which were according to the study hypotheses: Dominance of the right style in the study sample, and there were no statistically significant correlation between styles of learning and thinking (right, left, integrated) and the attitude towards Mathematics. At last, the study concluded with a set of recommendations and suggestions..
من ذوي صعوبات تعلم الرياضيات وعلاقتها بالاتجاه نحو مادة الرياضيات
مقال
Keywords: أنماط التعلم والتفكير; الاتجاه نحو مادة الرياضيات; صعوبات تعلم الرياضيات; styles of Learning and thinking; the attitude towards mathematics; learning disabilities in mathematics